ANALISIS TINGKAT PENGANGGURAN TERBUKA BERDASARKAN INDIKATOR SOSIAL DI PROVINSI KEPULAUAN BANGKA BELITUNG MENGGUNAKAN PENDEKATAN REGRESI B-SPLINE - Khoirun Laili Nur Amaliah; Diska Amalya; Nila Selviana; Muthia Afrilita; Dea Saskia Amanda Putri; Ineu Sulistiana (Jurnal Gaussian, 2025)
The Open Unemployment Rate (TPT) is usually an important indicator in assessing the level of effectiveness of regional development in providing employment. In the Bangka Belitung Islands Province, the dynamics of the TPT have shown a fluctuating pattern over the past few years. The fluctuation of the TPT can be caused by several social indicators such as the Labor Force Participation Rate (TPAK), the Gross Participation Rate (APK) of upper education, and the Poverty Depth Index (P1). Judging from the data obtained, the form of data that has an irregular pattern, the method used in this study is b-spline regression which can capture fluctuating patterns in the data. The results show that the b-spline model is very good at capturing fluctuating patterns in the Open Unemployment Rate with several other social indicators seen from the MAE value of 0.05879, RMSE of 0.081630 and Adjusted R-squared of 0.7206 indicating that the b-spline regression model is able to explain around 72.06% of the variation in the response variable. Based on the results of the simultaneous test, it shows that variable have a significant effect on TPT, while the partial test it shows APK SMA and P1 have a significant effect on TPT.